7.2 notes

# 7.2 notes - Chapter 7 The laplace Transform §7.2 Inverse...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 7. The laplace Transform §7.2 Inverse Transforms and Transforms of Derivatives 1. Inverse Transforms: Let F (s) be a Laplace transform of a function f , i.e. F (s) = L{f (t)}, we then say f (t) is the inverse Laplace transform of F (s) and write f (t) = L−1 {F (s)}. Ex: Find the Inverse Laplace transform. ￿￿ ￿￿ 1 1 1 = L−1 , t = L−1 2 s s L−1 is a linear transform: i.e. L−1 (αF (s) + β G(s)) = αf (t) + β g (t) Theorem: Some Inverse Transforms. 1. 1 = L−1 2. 3. 4. 5. ￿￿ 1 s. ￿ ￿ n! tn = L−1 sn+1 , n = 1, 2, 3, . . . . ￿ ￿ 1 eat = L−1 s−a . ￿ ￿ k sin kt = L−1 s2 +k2 , cos kt = ￿ ￿ k sinh kt = L−1 s2 −k2 , cosh kt L−1 = ￿ s s2 +k 2 . ￿ ￿ s L−1 s2 −k2 . ￿ Ex: Find the Inverse Laplace transform. ￿￿ ￿ ￿ ￿ ￿ 1 1 −2s + 6 L−1 5 , L−1 2 , L−1 s s +5 s2 + 4 ￿ ￿ s L−1 2 s + 2s − 3 2. Transforms of Derivatives Theorem: If f, f ￿ , . . . , f (n−1) are continuous on [0, ∞) and are of ex1 ponential order and if f (n) is piecewise continuous on [0, ∞), then L{f (n) } = sn F (s) − sn−1 f (0) − sn−2 f ￿ (0) − · · · − f (n−1) (0), where F (s) = L{f (t)}. 3. Solving Linear DEs: Solve DEs. 1. y ￿ + 3y = 3 sin 2t, y (0) = 2. y (0) = 1, y ￿ (0) = 5. 2. y ￿￿ − 3y ￿ + 2y = e−4t , 2 ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online